Preparative separation and purification of loliolide and epiloliolide from Ascophyllum nodosum using amine-based microporous organic polymer for solid phase extraction coupled with macroporous resin and prep-HPLC. Issue 16 (8th April 2021) - Chi, Hao; Qi, Xia; Wang, Xiaohui; Wang, Ying; Han, Xihong; Wang, Jiao; Wang, Hongwei
Abstract : Herein, we reported a novel approach for the separation and purification of loliolide and epiloliolide from A. nodosum by combined use of an amine-based MOP, a macroporous resin column and prep-HPLC. Abstract : Herein, we reported a novel approach for the preparative separation and purification of loliolide and epiloliolide from Ascophyllum nodosum . An amine-based microporous organic polymer (MOP) was used for the pretreatment of the nodosum extract via solid-phase extraction (SPE). The obtained extract was further purified using macroporous resin chromatography and preparative high-performance liquid chromatography (prep-HPLC). The loading and elution parameters of the MOP were evaluated using standard loliolide, and the optimized conditions were used during the SPE of the nodosum extract (37.5 g). After the pretreatment with MOP, the extract (2.79 g) was obtained and further purified using a D101 resin column followed by prep-HPLC. A pair of epimers were isolated and identified as loliolide (5.83 mg) and epiloliolide (2.50 mg) using high-resolution electrospray ionization tandem mass spectrometry (HRESI-MS), 1D- and 2D-nuclear magnetic resonance (NMR) spectroscopy. This study demonstrates the potential of MOPs in the separation and purification of monoterpenoids from complex plant samples.